Non-mercury catalytic acetylene hydrochlorination over activated carbon-supported Au catalysts promoted by CeO2. Issue 6 (3rd November 2015) - Li, Guangbi; Li, Wei; Zhang, Jinli
Abstract : Gold–cerium oxide catalysts were prepared to study the effects of cerium oxide additives on the catalytic performance of gold catalysts for acetylene hydrochlorination, using activated carbon as the support. Abstract : Gold–cerium oxide catalysts were prepared to study the effects of cerium oxide additives on the catalytic performance of gold catalysts for acetylene hydrochlorination, using activated carbon as the support. The optimal catalytic performance is achieved over the 1Au–5CeO2 /AC catalyst with an acetylene conversion of 98.4% and a selectivity to vinyl chloride monomer (VCM) of 99.9% after 20 h on stream under the conditions of 180 °C, C2 H2 gas hourly space velocity (GHSV) of 852 h −1 and HCl/C2 H2 feed volume ratio of 1.15. It is indicated that the addition of cerium oxide can make active Au species uniformly dispersed and improve the adsorption properties of reactants on the catalysts, but also suppress the reduction of active gold species and inhibit coke deposition on the catalyst surfaces during the reaction. Characterization was carried out using transmission electron microscopy, Raman spectroscopy, N2 adsorption/desorption analysis, thermogravimetric analysis, temperature-programmed reduction, temperature-programmed desorption, powder X-ray diffraction, atomic absorption spectroscopy and X-ray photoelectron spectroscopy.